EXAMINING UTILIZATION OF HOSPICE AMONG MEDICARE/MEDICAID DUALLY ELIGIBLE AND MEDICAID-ONLY DECEDENTS. (11th November 2018) - Robison, J; Migneault, D; Kubisiak, J; Mitchell-Daniels, M; Cherlin, E; Wang, S; Lambert, D
Abstract: The 2017 AARP LTSS Scorecard reported that Connecticut ranked 51st nationally in the percent of home health patients that have a hospital admission and falls behind other states in utilization of palliative care. Home health providers suggest underutilization of hospice as a primary driver of high hospital admission rates. The study, funded by the Connecticut Department of Social Services, aimed to improve understanding of hospice utilization among Medicare/Medicaid dually eligible and Medicaid-only populations. Results of analysis of Medicaid-only (n=2, 979) and Medicare/Medicaid dually eligible (n=12, 090) decedents' Medicare and Medicaid claims data from 2014 through 2016 showed that dually eligible decedents had a significantly higher rate of hospice use compared to Medicaid-only decedents (44% vs. 18%) and a significantly longer average length of stay in hospice (49.65 vs. 26.58 days). Dually eligible hospice users are more likely to have a diagnosis of Alzheimer's disease and related disorders (47%) compared to Medicaid-only hospice users (19%). Other diagnoses show similar patterns. Geographic variation across regions was not substantial, indicating that the observation of low hospice use is a state-wide issue. Approximately 50% of hospice use was potentially concerning, including hospice dis-enrollment and very short/long hospice enrollment. Additionally, the analysis examined utilization within the two groups of decedents. Findings suggest where there are divergences in hospice utilization within Dual and Medicaid only populations. Recommendations include encouraging physician use of hospice/palliative screening tools and developing education interventions with physicians and patients to increase the understanding of the benefits of hospice and palliative care.